COASTAL TOURISM DEVELOPMENT: GUIDING PRINCIPLES FOR SUSTAINABLE DEVELOPMENT - Derrin Davis (JOURNAL OF COASTAL DEVELOPMENT, 1998)
The paper is based on the preparation by the author and two colleagues1 of a report on principles of sustainable development in Australia’s coastal zone, with a specific focus on the tourism industry. That report, prepared with funding under Australia’s Coastal Action Program, and following public comment and revision, has recently been published by the Australian Government under the title Coastal Tourism: A Manual for Sustainable Development (Commonwealth Coastal Action Program, 1997). The coast is an important part of the tourism industry’s attraction and resource base in Australia and many other countries. It is concluded that sustainable development and use of the coastal zone is crucial to the long-term profitability of the tourism industry and the quality of life of local citizens. The stage of the development process – from feasibility to operation and management – are each considered of importance to sustainable tourism developments. A number of guiding principles for such developments are spelled out in the paper, and issue such as self-regulation and the reasons that developers should consider sustainability in their activities are addressed. Additionally, reference is made to case-studies of sustainable tourism development that have occurred in Australia in recent years, and the lessons from those developments described. The key recommendation arising is that a valuable contribution to protecting coastal assets – assets upon which the tourism industry and the community depend – will arise from the formulation of environmental, social and economic criteria that developers can consider in planning, constructing and operating tourism ventures in the coastal zone.